Anti‐α4 Integrin Antibody Blocks Monocyte/Macrophage Traffic to the Heart and Decreases Cardiac Pathology in a SIV Infection Model of AIDS. Issue 7 (July 2015) - Walker, Joshua A.; Beck, Graham A.; Campbell, Jennifer H.; Miller, Andrew D.; Burdo, Tricia H.; Williams, Kenneth C.
Abstract : Background: Cardiovascular disease (CVD), myocarditis and fibrosis are comorbidities of HIV + individuals on durable antiretroviral therapy (ART). Although mechanisms for these vary, monocytes/macrophages are increasingly demonstrated to be key players. Methods and Results: We directly blocked monocyte/macrophage traffic to the heart in an SIV model of AIDS using an anti‐alpha‐4 integrin antibody (natalizumab). Nineteen Rhesus macaques were SIVmac251 infected and CD8‐lymphocyte depleted for the development of rapid AIDS. Ten animals received natalizumab once a week, for 3 weeks, and were sacrificed 1 week later. Six animals began treatment at the time of infection (early) and the remaining 4 began treatment 28 days post‐infection (late), a time point we have previously established when significant cardiac inflammation occurs. Nine animals were untreated controls; of these, 3 were sacrificed early and 6 were sacrificed late. At necropsy, we found decreased SIV‐associated cardiac pathology in late natalizumab‐treated animals, compared to untreated controls. Early and late treatment resulted in significant reductions in numbers of CD163 + and CD68 + macrophages in cardiac tissues, compared to untreated controls, and a trend in decreasing numbers of newly recruited MAC387 + and BrdU + (recruited) monocytes/macrophages. In late treated animals, decreased macrophage numbers in cardiac tissues correlated with decreased fibrosis. Early and late treatment resulted in decreased cardiomyocyte damage. Conclusions: These data demonstrate a role for macrophages in the development of cardiac inflammation and fibrosis, and suggest that blocking monocyte/macrophage traffic to the heart can alleviate HIV‐ and SIV‐associated myocarditis and fibrosis. They underscore the importance of targeting macrophage activation and traffic as an adjunctive therapy in HIV infection.